Trends, Thematic Maps, and Collaboration Networks in Singapore's Multicultural Counseling Research: A Bibliometric Review - Faizal Ramley; Muhammad Ilham Bakhtiar; Rahmaeni; A. Agustan Arifin; Idriani Idris; Hadryanti (ILIN Education Indonesia, 2026)
The purpose of this study is to determine (1) the development trends of multicultural counseling research analysis in Singapore based on bibliometrics; (2) Main themes, study focus, and research trend topics in multicultural counseling studies in Singapore; (3) Research collaboration in multicultural counseling studies in Singapore. The study uses bibliometric analysis with data from OpenAlex totaling 600 manuscripts for the period 2020–2026 using the search query TITLE-ABS-KEY (